Effect of Four Antioxidants Combination on Number of Sertoli and Leydig Cells, Sperm Quality and Caspase-3 Expression in Rat Exposed to Cigarette Smoke - Yuniarifa, Conita; Wibowo, Joko Wahyu; Nasihun, Taufiqurrachman (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Introduction: The administration of antioxidant combination has been shown to be more effective than that of individual antioxidant in male infertility.Objective: to determine the effect of different combination of antioxidants (vitamin/vit C, vit E, glutathione and zinc) on the number of Sertoli and Leydig cells, sperm quality and texpression of caspase-3 in rats exposed to cigarette smoke.Methods: This was an experimental study using a post test only control group design. Thirty six rats were randomly divided into 6 groups to receive one of the following combinations of antioxidants: vit C and E, glutathione, zinc (T4-G); vit C and E, glutathione (T3-G); vit C and vit E (T2-G); Glutathione, zinc (T1-G); control positive (CP-G) cigarette smoke exposed only, normal (CN-G). The dose of vit C, vit E, glutathion and zinc was 9 mg/day, 1.8 IU/day, 1.8 mg/day, 0.2 mg/day respectively. All groups were exposed to cigarette smoke (3 cigarettes/day for 21 days), except for the CN-G group. On day 22, sperm samples were taken. Testicular tissue was taken for measurements of sperm quality, sertoli and leydig cell.numbers.Results: There was a significant difference in mean number of Leydig cells, sperm motility, sperm count and caspase-3 between groups (p<0.05). Post hoc LSD showed that the administration of combination of four antioxidant agent increasing the number of Sertoli cells and sperm morphology. The results also showed that group treated with 4 antioxidants combination had the highest number of Leydig cells, sperm motility, sperm counts and the lowest expression of caspase-3.Conclusion:The combination of vitC, vit E, glutathione and zinc affects the number of Sertoli and Leydig cells, sperm quality, expression of caspase-3 in rats exposed to cigarette smoke .